Pelatihan Pencarian Literatur yang Kredibel Menggunakan AI dalam Penulisan Karya Ilmiah bagi Mahasiswa di Merauke - Hajra Yansa; Aser Parera; Dite Umbara Alfansuri; Yulia Olga Siba Sabon; Haerul Amri; Abdullah; Muh. Rafi'y (Jurnal Transformasi Pendidikan Indonesia, 2025)
To succeed in academic writing, students must have the ability to locate and evaluate reliable scientific literature. However, many students still experience difficulties in searching for relevant reference sources. Therefore, this community service aims to improve students' academic information literacy by teaching them how to use Artificial Intelligence (AI) in searching for credible literature. An initial needs survey, guidebook preparation, hands-on implementation, and barrier analysis to evaluate the training results were used in this activity. This service involved 22 students in Merauke Regency, South Papua Province. The results showed that students were better able to use AI to find and validate scientific reference sources. The stages of service include, FGD with lecturers, surveys on students, preparation of guidebooks, training, and analysis of obstacles. Most participants who previously did not know how to distinguish credible sources can now use better search strategies by using various AI platforms, such as Scite AI combined with GPT in writing academic work. Device limitations were the main obstacle in this training.